Identifying The Components And Factors Of Graduate’s Employability: The Perspectives Of Policymakers, University Administrators, Undergraduates And Employers In Penang - Hao, Moo Keng (2023)
There numerous of study about employability has been conducted by researchers from different discipline previously. However, the research that conducted did not touch on all four stakeholders that this study looks into. Beside that, the unemployment rate of Malaysia is having the trend of increase yearly, and effort that taken are not uniform. Therefore, this study explored the concept of employability by unpacking this from the perspectives of policymakers, university administrators, employers and undergraduates. Policymakers, university administrators representatives, employer representatives and undergraduate representatives were recruited as participants in this study. These respondents were selected because they are the ones who produce the direct impact and direct beneficiary of employability. Data for policymakers was collected through the policymaker who is from the Ministry of Higher Education, whereas the university representatives are from a public research university in Penang and an international college in Penang. While for employers, the chosen employers' representatives are those who are involved directly in the recruitment process of that particular company. Lastly, student representatives are the students who are still studying at the public research university and the international college in Penang. Qualitative data were collected using semi-structured interviews as instruments. Results showed that employability is a process, and it has four characteristics which are job suitability, ability to be employed, readiness of employment and job sustainability. The study also found that employability skill can be interpreted in both the short-run and long-run. Skill-based employability and knowledge-based employability primarily contribute to short-term employability, while competence-based employability and capability-based employability, along with the other two employability types, contribute to long-term employability for graduates.